A Business Law Review on the Unauthorized Use of Product Photos That Infringe Copyright on Digital Marketplaces - Dewi Yustiana (Fox Justi : Jurnal Ilmu Hukum, 2025)
The rapid development of digital commerce has impacted the pattern of intellectual property rights violations, particularly copyright infringement of product photos on marketplace platforms. The unauthorized use of product photos by third parties often occurs and is frequently underestimated, even though such actions constitute copyright violations regulated under Law Number 28 of 2014 concerning Copyright. This study aims to review the legal business protection for copyright owners of product photos misused on digital marketplaces, as well as to analyze the responsibilities of business actors and platform providers. The method used is a normative juridical approach with legislation review and literature study. The results show that legal protection against copyright violations in the digital realm remains suboptimal, especially in terms of law enforcement and platform supervision. Strengthening regulations, socialization to business actors, and raising legal awareness among marketplace users are needed to prevent similar violations in the future.